Tax Avoidance Measures in Food and Beverage Sub-Sector Manufacturing Companies in Indonesia 2019-2021 - Erlina Djatnicka; Ahmad Bukhori Muslim; A’zzah Fadillah (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to determine the effect of audit committees, fixed asset intensity, and profitability on tax avoidance in food and beverage sub-sector manufacturing companies listed on the IDX in 2019–2021. The analytical methods used are the descriptive analysis method, the classical assumption test, and the hypothesis test. The conclusion of this study shows that the audit committee has a tcount value with a negative sign of 0.202 < ttable 2.010 and a significance value of 0.481 > 0.05, which means the audit committee has no significant effect on tax avoidance. The intensity of fixed assets has a tcount of 0.515 < ttable of 2.010 with a significance value of 0.609 > 0.05, which means that the intensity of fixed assets has no significant effect on tax avoidance. Profitability has a negative tcount value of 2.905 table 2.010 with a significance value of 0.006 < 0.05, which means that profitability has a significant effect on tax avoidance. Simultaneously, the audit committee, the intensity of fixed assets, and profitability have a significant positive effect on tax avoidance.